(untitled) (Research, Society and Development, 2021)
The bicycle is used as a means of transport and laser is easily accessible and also a favorable alternative for transportation, in addition to having an acceptable cost-benefit ratio and for promoting good health for its riders. As with every sport, there is somehow a factor that leads to an injury risk. This study aimed to analyze the musculoskeletal effects that occur in amateur cyclists in a group in the city of Santarém/PA. The research took place in Santarém, Pará, with an organized group of amateur cyclists who cycle regularly on a weekly basis and the study consisted of 18 cyclists. As a tool for data collection, an existing questionnaire on quality of life using the SF-36, which is a global instrument created by Ciconelli et al. (1999) and the Nordic Muscle/Skeletal questionnaire by Kourinka et al. (1989). The data obtained were analyzed using quantitative descriptive statistics, using frequency tables. In the sample, females had greater participation than males, since 56% were women. It is concluded that the profile of cyclists who are members of the sample shows that anatomical regions of the lumbar spine and knee regions were the most predominant areas for complaints of pain when compared to the other regions and that the thoracic region proved to be a poor area. relevant to injuries in these amateur cyclists and that the sample showed no difficulty or limitation in practicing their rigorous activities of the day or sports.